ESTRO guidelines for developing questionnaires in survey-based radiation oncology research - Amanda Webster; Lotte S. Fog; Emma Hall; Peter S.N. van Rossum; Daan Nevens; Pierre Montay-Gruel; Pierfrancesco Franco; Elizabeth Joyce; Nuria Jornet; Catharine H. Clark; Jenny Bertholet (Clinical and Translational Radiation Oncology)
Survey-based research is increasingly used in radiation oncology, yet survey-based research methodology is often unfamiliar in the field. This guideline offers comprehensive instructions for conducting survey-based research in radiation oncology, covering critical aspects such as survey design, validation, dissemination, analysis, and reporting. Tailored to professionals, it emphasizes the importance of methodological rigour to ensure reliable and actionable data collection. Dissemination strategies are highlighted to maximize response rates and enhance data completeness across diverse clinical, research and industrial settings. Rigorous analysis techniques are discussed to uncover insights that optimize operational efficiencies and inform evidence-based practices. Transparent reporting is underscored as crucial for enhancing the credibility and applicability of findings. This guideline aims to be a practical resource for enhancing research standards in survey-based research for researchers and practitioners in radiation oncology.